Nitrogen deposition mitigates long-term phosphorus input-induced stimulative effects on soil respiration in a tropical forest - Xingyun Huang; Yingwen Li; Shiqin Yu; Yongxing Cui; Fangyuan Guan; Yongxing Li; Jingtao Wu; Yang Hu; Zhian Li; Ping Zhuang; Bi Zou; Guoming Qin; et al. (Geoderma)
Atmospheric nitrogen (N) deposition and anthropogenic phosphorus (P) input simultaneously affect soil respiration (RS), a crucial process that mediates soil carbon (C) cycling. However, the interaction of N deposition and anthropogenic P input on RS, as well as its components—autotrophic respiration (RA) and heterotrophic respiration (RH)—remain largely unexplored. Herein, we conducted an 8-year field experiment with N and P additions in a tropical secondary forest, integrating the vegetation traits, soil physicochemical properties, organic C fractions, and microbial properties, to explore the effects of nutrient inputs and their interactions on RS, RA, and RH. Over eight years, along P input significantly increased RS by 19.2% and RH by 42.1%. These increases were partially mitigated (by 33.2% annually for RS and 58.3% annually for RH) with the addition of N. In contrast, the co-addition of N and P enhanced RA compared to alone N or P addition, suggesting that N deposition mitigated the stimulative effect of P input on RS by reducing RH rather than RA. The structural equation model further revealed that N deposition reduced RH primarily by increasing soil N:P ratio and decreasing both the labile C fraction and fungi biomass. Our findings suggest that prevalent N deposition across low latitudes could have substantially mitigate C emissions from forest soils under anthropogenic P input.